(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Desertion in higher level educational institutions; its study and monitoring has become relevant in recent years; on the one hand, being one of the main problems they face; increasing for reasons of the pandemic and that undoubtedly affected the student sector and on the other, by trying to maintain institutional educational quality, being one of the indicators evaluated by the country’s accrediting bodies in all educational programs. What is exposed here is the first phase of an investigation developed to know the desertion factors in the students of the Bachelor of Administration and Bachelor of Public Accounting of the Department of Administrative Economic Sciences of the Southern Regional Unit of the University of Sonora. This stage had the purpose of identifying the cases of students registered in the periods 2018-2, 2019-2 and 2020-2 who had abandoned their careers by the 2021-2 cycle and their proportion in the period of confinement and who currently had to attend the fourth, sixth and eighth semester. The total population analyzed was 200 students from the two programs, finally accounting for a dropout of 15 CP and 23 LA in the cohorts. These results have made it possible to start the next phase of the study to find out the reasons for their desertion.